A semântica dos adjetivos: como e por que incluí-la em uma ontologia de domínio jurídico - Bertoldi, Anderson (Universidade do Vale do Rio do Sinos, 2007)
The main goal of this research is to study the semantics of the adjectives in order to codify them into a legal ontology. Through a search for legal ontologies and lexicons one verifies that adjectives are not codified systematically into specialized lexicons and ontologies. Taking the codification of adjectives into a legal ontology as the target of this work, one analyzes non-specialized language ontologies and lexicons. The purpose of such analysis is to find practical and theoretical elements for including adjectives systematically into a legal ontology. This research defends the position that integrating linguistic approaches is more fruitful to natural language processing. Therefore, the methodology applied here combines different theoretical approaches. The corpus analysis and legal ontology construction shows the importance of adjectives in organizing the specialized knowledge. In the specialized domains, adjectives have the main function of classifying entities
Keywords: adjetivo; computação; direito; linguagem; ontologia jurídica; lingüística computacional; semântica; adjectival valency; legal terminology; lexicon; ontology; semantic networks; adjective: lexical semantics; Letras e Artes; Lingüística